Promoting Well-Being of Children at School: Parental Agency in the Context of Negotiating for Support - Koskela, Teija (Frontiers in Education, 2021)
This study describes how parents experience their role in enhancing the well-being of their children and what this reveals about parental agency in the context of collaborations between home and school. In Finland, schools are among the most important environments for delivering services to children. The goal of this study is to bring into focus the parental dispositions in multi-agency interactions based on their experiences and to make sense of both their successes and the barriers they face. The Finnish education system aims to develop itself according to the inclusive principles. However, the inclusive school culture is still a work in progress. The parental agency and positions in collaboration with school personnel are ambivalent, and there are several assets and barriers that affect their ability to participate fully in discussions about the well-being of their children at school. In this article, the parental positions are connected to situations where they negotiate the process of collaborative planning of support for the learning and well-being of their children in the school environment. Participants are 13 mothers and one couple, mother and father. Their experiences are analyzed qualitatively via interviews and the concept of agency, a sociological concept that refers to the mutual relation between a culture or structure and the opportunities of human agents to interact within the given contexts. The results reveal qualitative differences in the experienced parental agency. The parental agency is connected to the given opportunities, and the key role in making the agency possible in the schools is given for the teachers. Behind everyday practices, there are deeper questions about the parental positions and their value in collaboration.